AN ANALYSIS OF CODE MIXING BY PREACHERS IN MAWAR SHARON CHURCH - FIRESTA SOEPRAYOGI, EVA (Language Horizon: Journal of Language Studies, 2014)
AN ANALYSIS OF CODE MIXING BY PREACHERS IN MAWAR SHARON CHURCH Eva Firesta Soeprayogi English Literature, Faculty of Languages and Arts, Surabaya State University commit_fg@yahoo.com Adam Damanhuri, S.S., M.Hum English Department, Faculty of Languages and Arts, Surabaya State University adamdamanhuri@gmail.com Abstrak Saat ini, code mixing menjadi fenomena bahasa. Pertama,code mixing tersebut dapat diterapkan diantara interaksi social dalam komunikasi bilingual masyarakat. Kedua, karena ada banyak orang, termasuk seorang artis juga menggunakan code mixing. Penelitian ini adalah tentang code mixing yang terjadi dalam situasi formal yaitu disebuah gereja di Surabaya. Penelitian ini berkaitan dengan ucapan-ucapan yang diucapkan oleh pendeta di Gereja Mawar Sharon yang dapat dinamakan sebagai MSC, terutama dalam ibadah kaum muda. Penelitian ini difokuskan pada code mixing yang terjadi di MSC. Tujuan dari penelitian ini adalah untuk menggambarkan bagaimana code mixing yang terjadi di MSC. Deskripsi ini meliputi: (1) jenis code mixing antara bahasa Indonesia dan bahasa Inggris yang digunakan oleh pendeta di MSC, (2) alasan mengapa mereka menggunakan code mixing. Peneliti menggunakan metode deskriptif kualitatif dan (Miles &Huberman, 1992, hal. 20) teori untuk teknik analisis data. Dalam analisis, peneliti melakukan beberapa proses analisis, yaitu, (1) daftar data, (2) mengklasifikasi data sesuai dengan jenis dan alasan, (3) menggambarkan bagaimana code mixing terkait dengan masing-masing teori yang sesuai dengan teori (Musyken 2000), (Hoffman, 1991), dan (Pardede &Kisno, 2007). Hasilnya menunjukkan bahwa semua teori dalam bab dua adalah sesuai dengan data yang telah dikumpulkan. Semua ucapan-ucapan dari para pendeta di MSC berhubungan dengan teori bilingualism dan status sosial. Mereka membuat bahasa Inggris sebagai bahasa yang tinggi dan menggunakan bahasa tersebut untuk memeriksa isi Alkitab. Ketika pendeta tersebut hendak memberikan informasi atau pengetahuan, mereka pasti mencampur bahasa mereka . Kata Kunci: Bilingualisme, Status Sosial, dan Code Mixing Abstract Nowadays, code-mixing becomes phenomena of language. Firstly, the code mixing can be applied among social interaction in bilingual communication and society Secondly, because there are many people, including an artist who also uses code mixing. In this research is about code mixing that happens in formal situation where it is in a church in Surabaya. This research deals with utterances that are spoken by preachers in Mawar Sharon Church, it can be named as MSC, especially in youth matins. This study is focused on code mixing that happens in MSC. The purpose of this study is to describe how code mixing happens in MSC. The description includes: (1) types of code mixing between Indonesian and English used by preachers in MSC, (2) the reasons why they use code mixing. The researcher applies descriptive qualitative method and (Miles & Huberman, 1992, p. 20) theory for data analysis technique. In the analysis, the researcher does some process of analysis, they are (1) listing the data (2) classifying the data according to the types and reasons (3) describing how code mixing related to each theories are flouted by (Musyken, 2000), (Hoffman, 1991), and (Pardede & Kisno, 2007). The result shows that all of the theory in chapter two is appropriate with the data that have been collected. All of the utterances from the preachers in MSC are related with theory of bilingualism and social status. They make English language as a high language and use the language to examine the contents of the Bible. When she or he wantsto give information or knowledge, they certainly mix their language. Keywords: Bilingualism, Social Status, and Code Mixing INTRODUCTION This study is about code mixing that happens in Mawar Sharon Church using natural data collected from preacher of Mawar Sharon, it can be named as MSC. MSC is a name of non-denominational charismatic church in Surabaya and the location is on Jalan Cempaka. In MSC, there are 3 matins. The first is for Sunday school, the second is for youth and the last matins is for adult. In this case, the researcher focused in youth matins. In every matins, there is a preacher who always gives sermon to their members. In addition, the preachers are also from different background of family who has been from business family background such as in export – import business. An export-import business, also known as international trading is one of the hottest commercial trends of this decade (WiseGeek, 2003). People who have a business in the export – import business have to speak with English language since English language is an International language (Neeley, 2009, p. 117). So, they must force themselves to learn English language and certainly they are from educated people because the businessman is good at dealing with business and financial matters and works in in a high position (Incorporated, 2004). Although, some of them have English language as their first language and Indonesian language as their second language to speak with each other, but when they give a sermon to their members in the church, they still use Indonesia language and sometimes mix their language with English language. In Indonesia, mixing language between Indonesian and English is a common thing to do. It has become part of the culture for Indonesians to mix English with their language in their daily conversations, even though they are different in grammar and lexicon. Therefore, grammatically, English has patterns which are not same to Bahasa Indonesia patterns including the affix for verb, noun, and adjective and also the word order in phrases. In the other hand, both English and Bahasa Indonesia have similarity. English and Bahasa Indonesia have standard or formal and informal form which used in different situation as (Crystal, 2010, p. 228). The term of code-mixing is used following (Musyken, 2000, p. 1) refers to all cases where lexical items and grammatical features from two languages appear in one sentence. The focus of interest will be on “intra-sentential mixing” or mixing where elements from both languages appear in the same sentence. The writer focused on sociolinguistic in study how code mixing is used in the MSC: (1) What are types of code mixing between Indonesian and English used by preachers in MSC; (2) Why does code mixing between Indonesian and English happen in MSC. The significance of the study is to make the readers get information and increase knowledge about code mixing between English and Indonesian language and its application that can be found in community and the reason why people use code mixing in their utterance. Several theories are applied in conducting this study. The first theory is bilingualism by Bloomfield in (Chaer & Agustina, 2004, p. 85). He said that bilingualism as they the ability of two languages equally as a speaker and as the native speaker mastering the language. Another theory used in this study is from (Maise, 2004), it is about social status. The last is using theory from (Musyken, 2000) for types of code mixing and (Hoffman, 1991, p. 116), for reasons of code mixing. RESEARCH METHOD This research is designed to explore code mixing used by MSC members. The suitable method of this research is by descriptive qualitative method. This research is categorized as descriptive qualitative research as the way of generalizing the data is based on the phenomena gathered from the field.This method should be able to show the theoritical linguistics featured (Powell & Renner, 2003, p. 1) and qualitative research methods are usually associated with inductive approaches (based on empirical evidence) (Wyk, p. 16). Since this study focuses in utterance of preachers in MSC, so, the subject of this research is preacher in MSC especially in youth matins who can speak more than one language and they are from businessman background family. Meanwhile source of the data is sermons of the preacher and the data is preachers’ utterances. Then, the instruments of this study are observation is applied as the mean to find out the answers of the research questions. The researcher observes some conversations from members of MSC, come near to the members who do a conversation using code Mixing (English-Indonesia) and record their conversation using voice recorder and questionnaire is applied to get needed information from respondents. Notes and pen, voice recorder and other electronic devices are used as the tools to support the instruments and data in conducting this study. In conducting data analysis in his research study the researcher uses some procedures and techniques. There are three steps of analyzing data: data reduction, data display, conclusion, and verification (Miles & Huberman, 1992, p. 20). DATA ANALYSIS AND DISCUSSIONS In this study, in analyzing code mixing, the researcher tried to find some types of code mixing and the following reasons why code mixing used by preachers in MSC. In presenting data analysis, each data will be explained by the type of code mixing according to the English language that have mixed in their utterances of Indonesia language because in this case, mostly the members used Indonesia language rather than English language. Based on the research which has been conducted in MSC, there are several types of code mixing that used by the preachers in MSC. (Musyken, 2000) has given types of code mixing. The researcher found that preachers in MSC always uses code-mixing in their utterances. Insertion The first type is insertion. Preachers of MSC can mix their language into Indonesia mostly because of this type. In the insertion pattern, one language determines the overall structure into which constituents from the other language are inserted. This type is According to (Musyken, 2000, p. 7 ). This datum is taken from utterance of a sermon from Ps. PM. His sermon is about true story behind the book of Ruth. This theme is taken from Holy Bible. The data is taken on February when there was an event called Valentine’s Day. The preacher mixes his utterance with English language. His utterances are taken according to the topic or when he changes the verse in Bible. Data Type Ketika kita baca kitab Ruth, meskipun ini romance antara ruth dan boas, tapi sebenarnya Tuhan sedang mau bicara lewat pembacaan kita. (When we read the book of Ruth, we think that it is about a romance between Ruth and Boas, but actually God is willing to talk with us through our reading). Insertion From the utterance, the linguistic unit of the English language “romance” is a word (see appendix 1 data no.40). The word “romance” is an insertion of material (lexical item) which is from English language into Indonesia structure sentence. It is appropriate with study of Musyeken (see chapter 2) about insertion of code mixing. In this case, the word “romance” is constructed by free morpheme because can stand alone as independent word and has meaning as an intimate relationship between two people. The word “romance” isa noun as a single word of English language and becomes the recipient of the action of the predicate in the sentence. It is clear that the speaker here was influenced by English language and put the English word as noun. So, the English word “romance” as noun is just a kind of juxtaposition. It does not violate the grammatical system of the Indonesia sentence. Alternation Musyeken said that alternation occurs when two languages are alternated indistinctively both at the grammatical and lexical level. It is alternation between structures from languages. Alternation is the constraint of mixing in terms of compatibility or equivalence of the languages involved at the mix point, and clause and the characteristic of alternation code mixing usually from Indonesia into English sentence. In this case, the researcher found that there was also type of code mixing, alternation, in the sermons of preachers in MSC. This datum is taken from Ps. PM utterance. There was utterance that appeared in sentences. “Nah, ketika itu mereka diam di Moab. Moab hari ini dijaman modern sekarang, Moab itu negeri Yordania. Ya, kita kemarin pergi ke Israel, tahun lalu, itu lewat suatu tempat kota namanya Aman. Aman itulah Amon.Jadi disini, di negera modern, Jadi Tuhan, tidak pernah menghendaki Eliyakin, Elimelekh, kok Eliyakin daritadi. Elimelekh, Naomi dan juga setengah mati dan mati-matian, dan sakit-sakitan, tidak pernah menghendaki mereka, berada di Moab, when God wants you in Church, where are you? In those examples, the alternation between English and Indonesia occur single turn. Indonesian English Jadi, [Tuhan tidak pernah menghendaki Eliyakin, Elimelekh, kok Eliyakin daritadi. Elimelekh, Naomi dan juga setengah mati dan mati-matian, dan sakit-sakitan][ Tuhan tidak pernah menghendaki mereka] [berada di Moab]. [When God wants you in Church] [where are you?] The English language from “when God wants you in Church” and “where are you?” is a sentence. While Indonesia language “Jadi Tuhan, tidak pernah menghendaki Eliyakin, Elimelekh, kok Eliyakin daritadi. Elimelekh, Naomi dan juga setengah mati dan mati-matian, dan sakit-sakitan, tidak pernah menghendaki mereka, berada di Moab” are also a sentence.From the data on the table, both of the languages are equivalence because both of the structures from the sentence have language with their own constituent structure. In the first, Ps. PM told to his members about Elimelekh families who stayed in Moab whereas God had given them a warning and he still told about his trip in Israel, he told about the life of Eliemelekh according to the book of Ruth and gave an explanation about a city in Yordania. He told about a history. After that, He changed the topic by using English language. He wanted to tell about the condition of his members right now, he switched his language become English language to gain attention from his members and make them understand about what he talked about. Congruent Lexicalization The third type is about congruent lexicalization. In the studies summarized in Muysken (2000: chap. 5), a standard language is mixed with a regional or social dialect in a continuously variable fashion. Such cases involve languages that are both lexically and structurally similar, presenting the most favorable environment for congruent lexicalization. From the data that has been collected, the researcher does not find uttereance or sentence that relates with this type because it is talking about regional dialect. Members just speak with Indonesia and English language while congruent lexicalization is related with regional dialect in variable fashion. Reasons of Preachers in MSC Using Code Mixing The main goal of this result was to analyze the reason of why the preachers in MSC used code mixing in their utterances. According to the theoretical background used in this analysis of the reason of the preachers of MSC used code mixing between Indonesia and English in their conversations, they are: talking about particular topic, quoting somebody else, being emphatic about something, interjection, repetition used for clarification, expressing group identity, intention of clarifying the speech for interlocutor, to soften request or strengthen command, real lexical needed and to exclude other people when a comment is intended for only a limited audience. Talking about a Particular Topic. In this case, when the preacher wants to talk about something in particular topic and express their emotional feeling she or he always prefers to speak it in English language as in datum 23, 24, 25 and 26. The datum is taken from the utterances of Ps. PM in timeline between 02:02 – 03:08 (see appendix 3 data 3 paragraph 3). In this case, the preacher gives an explanation about the topic of the true name of Ruth in book of Ruth. “Nama Ruth itu sebenarnya bagus sekali, boleh itu jika punya anak suatu hari kasih nama Ruth. Ya! Jangan salah spelling ya.Tapi kalau r-u-d-e itu rude tapi namanya nggak sopan. Ruth? Nah, itu Ruth ini. Dalam Bahasa Ibrani Ruth itu akarnya didalam Bahasa Ibrani ada dua akar, yang satu artinya beauty, yang satu artinya bukan beast,beauty and the beast, bukan! Yang satu beauty yang satunya lagi friend, jadi kalau kita gabung dua akar itu namanya Ruth itu sama dengan beautiful friend. Seorang sahabat yang cantik. Ya..seorang sahabat yang cantik. Manis sekali nama ini, ya!” The situation from the utterance is Ps. PM told his members about the true meaning of a name as his topic. The true name of Ruth is taken from Hebrew language. In this case, the preacher gives an explanation using English language to his members about the name of Ruth to get the sense of Ruth’s name because if he gives the meaning of Ruth in Hebrew, his members will not understand about it. When he talks about the meaning of a name, he uses English language to give the true meaning of someone’s name (see appendix 3 data 3 paragraph 3). In this case, he said that the name or Ruth has two meanings, they are beautiful and friend and it is combined to be a beautiful friend. Quoting Somebody Else From the data that have been collected, the preacher inserts English sentence or clause to quote a famous expression, proverb, or saying of some well-known figures. This datum is taken from the utterances of Ps. JM. “Oh ya ngomong-ngomong ada yang jadi designer nggak ya? Coba katakan gini: “(start to sing a song) “na nan a…gimana lagunya nothing is impossible? Nothing is impossible? “na nan a (laughing and clapping hand)…” In this case the phrase nothing is impossible was from a gospel song. Ps wanted to give it to encourage his member that whatever we do, there is not impossible with God. He took the words from a song because this song is popular. Being Emphatic about Something (express solidarity) The researcher has founded in the data that have been collected, when preachers want to being emphatic about something they either intentionally or unintentionally switch their language from first language to second language. This datum is taken from the utterances of Ps. JR., there was a sentence that shows about He being emphatic about something. “Dan saya mau beritakan kepada anda semua, terutama ladies, perhatikan!Ladies.Dalam relationship yang paling banyak menderita itu adalah yang wanita. Jadi, just be careful with yourself! Nah, Tuhan ciptakan kita sebagai makhluk yang relational, kita tidak diciptakan untuk sendirian……..” This datum is taken from the utterance of Ps. JR. The topic of his utterance is about dating. He gives an emphatic expression for his ladies members and gives a pressing in the English word “Ladies!”.He is so concerned about ladies who always be suffered in a relationship.He expresses his feeling of solidarity for ladies! Interjection In this case, Interjection is words or expressions which are inserted into a sentence to convey surprise, strong emotion, or to gain attention as in datum 31.This datum is also taken from the utterance of Ps. JR. “Well, apa yang saya mau bagikan bagi saudara ini adalah sesuatu yang sangat practical, saya tahu dalam waktu yang sangat singkat ini, saya tidak bisa berikan semuanya kepada saudara karena dan melihat begitu antusias saudara saya musti buat lagi suatu hari nanti ditempat yang jauh agak besar, sehingga saudara bisa belajar lebih lagi”. From the utterance above, the word “well” is used to connect with the sentence before. Ps. JR would to deliver his main topic about dating. Repetition Used for Clarification The researcher has found this reason from the utterances of preachers. When one of preachers uses English language, she or he also clarifies it with Indonesian English. They use repetition not only served to clarify what is said, but also to amplify or emphasize a message. This datum is taken from Ps. JM “Percaya, kalau kita setia sama Tuhan ada hal2 besar yang Tuhan siapkan yang kita nggak pernah pikirkan itu diberikan dalam kata yg pertama yg saya mau bahas adalah find it yang artinya adalah temukan itu”. In this case, the English sentence is “find it” and then the preacher gives clarification about the translation of what just he said in Indonesia language yang “artinya adalah temukan itu. Expressing Group Identity Code mixing can also be used to express group identity. The ways of communication of academic people, like preachers in their disciplinary groupings are obviously different from the other groups. In this datum, the researcher found about expressing group identity from the utterances of Ps. PM. “Selamat datang sekali lagi, saya senang sekali melihat, meskipun saya tahu ndak semua mengangkat tangan, biasanya, tapi angkat tangan atau yang ti- belum angkat tangan, high extend by welcomed to you, welcome kepada anda dan semoga anda bertumbuh ditempat ini, ya”. From the datum above, the preacher wants to express his feeling to the new members who for the first time join in this gathering. In MSC, there is an expression to greet new members who join in this community. He said “high extend by welcomed to you, welcome”. Intention of clarifying the speech content for the interlocutor When preacher talks to another bilingual/multilingual, there will be lots of code switching and code mixing occurs. A message in one code is repeated in the other code in somewhat modified for. This datum is taken from the utterances of Ps CN. “Dengan kata lain Bahasa inggrisnya unlearn. Kalau mempelajari itu learn. Tapi ada hal-hal lain yang perlu kita unlearn okey? The utterance above shown the reason of the utterances of Ps. CM is Intention of clarifying the speech content for interlocutor. He gave an explanation about the word “learn and unlearn To soften or strengthen request or command For Indonesian people, code switching and mixing Bahasa Indonesia to English language can be soften a request because English is not their mother tongue, so the sound does not as direct as Bahasa Indonesia. In this case, the preacher in MSC uses English language to give strengthen command or to give encourage for their members. This datum is taken from the utterance of Ps, “Dan kalau 10 tahun itu engkau hidup diluar kehendak Dia, kamu kehilangan banyak….kebaikannya dihidupmu, Comeback! Dia akanrestore!Dia akan memulihkan hidupmu”. From the utterance, the preacher gives a command for his members by using English word that inserted in the sentence. He told us that when we do something wrong and live outside God’s will, we can lose anything! His kindness! So, he uses the word “Comeback!” by using high tone and give a pressing in the word. Real Lexical needed The preacher in MSC also uses English language because she or he is lack in equivalent lexicon in the languages. When he or she is lacking in Indonesia, he will find it easier to say it in. This datum is taken from the utterance of Ps. PM “Berbicara tentang kekosongan, berbicara tentang, unblessingness, ya nggak tahu.hmmm Nggak tahu apa Bahasa inggrisnya unblessingness, itu apa ya! Tanpa berkat!” From the data above, the preacher is obviously lack in vocabulary. He hardly finds out the proper words for certain expression or word in their own language, they used foreign words which is in this case are English. By using the sentence “I do not know”, it proves that the preacher really needs the lexical. When he has a word that is lacking in Indonesian, he will use the English term. If it put into Indonesian, the meaning will be hazy or vague, and sometime it would not be used. To exclude other people when a comment is intended for only a limited audience Sometimes people want to communicate only to certain people or community they belong to. To avoid the other community or interference objected to their communication by people, they may try to exclude those people by using the language that no everybody knows. This datum is taken from the utterance of Ps. CN “Kita kan sudah ber- good morning Holy Spirit.Saya ingin anda tidak hanya ber- good morning Holy Spirit satu kali dalam satu tahun, tapi setiap hari waktu anda ber- good morning Holy Spirit kalau anda bangun pagi , From the utterance above, the preacher mentions about ber- good morning Holy Spirit. It talks about to do praying to have intimacy relationship with God every morning. In this case, just the members of MSC that already knows about the phrase because it is something likes as a term known only to the MSC members. DISCUSSIONS In the discussion section, the elaboration of the entire analysis that has been conducted is explained to present the final result. The discussion section consists of the types of code mixing and the reasons why preachers in MSC use code mixing will be discussed with the theories that have been applied and with the previous studies which are used in this study. From the data above, the members of MSC really use code mixing when they are speaking with the other. They are mixing of linguistic elements from two different languages, Indonesia and English language. It is appropriate with the theory code mixing from Musyeken. From the utterances that have been analyzed, it can be parted according to the linguistic unit (Bhatia & Ritchie, 2006) such as words, sentence, phrase, and clause. As predicted, the researcher finds insertion to be the dominant pattern in Indonesia-English code mixing data from preachers of MSC even in formal language. The researcher also finds the overall result is compatible with the insertion pattern. In the insertion itself, there is also the own type and it is also appropriate with the theory of code mixing from (Musyken, 2000, p. 7). This data is appeared in table form. For more detail information of this result see appendix 2. Findings Types of Insertion No. Utterances Linguistic Unit Type of Insertion in Code Mixing Speaker 1. Ketika kita baca kitab Ruth, meskipun ini romance antara ruth dan boas, tapi sebenarnya Tuhan sedang mau bicara lewat pembacaan kita. Word Noun Ps. PM 2. Nah berbicara mengenai 1, jangan main-main dengan yang 1, pake ukuran sack itu, 1 talenta itu sama dengan 34, aduh sudah belajar matematik. Word Noun Ps. JM 3. Mereka mengadakan event itu, mereka memanggil dia dan dia datang, dan mereka memberikan dia sesuatu, mengingatkan dia kembali akan siapa dia sebenarnya, dia adalah seorang prajurit. Word Noun Ps. CN 4. Dan kenapa marriage, kenapa pernikahan banyak yang amburadul, karena hampir tidak ada orang yang belajar mengenai pernikahan. Word Noun Ps. JR 5. Dan akhirnya dia meninggalkan rumahnya, keluarganya, dan hidupnya mabuk-mabukan dan hancur dan menjadi homeless bertahun-tahun. Word Adjective Ps. CN 6. Naomi itu Bahasa aslinya artinya, pleasant atau menyenangkan. Word Adjective Ps. PM 7. Kalau saudara perhatikan baik-baik, waktu Tuhan, present, ambil rusuk dari adam, dan bentuk hawa, dia nggak pernah paksa adam untuk menikahi hawa. Word Adjective Ps. JR 8. Saya kalau ke gereja kegereja karena diundang, ada yang purposely saya belajar. Word Adverb Ps. JM 9. Sekali lagi kalau saya jadi lawyer-nya Tuhan, pengacaranya Tuhan, saya akan ngomong. Word Adverb Ps. PM 10. Mau moderen dance, mau apa?. Bener, saya suka masuk drama, maen lenong saya suka Phrase Noun Phrase Ps. JM 11. Tapi check list itu menceritakan tentang hal–hal yang salah atau tindakan yang menyakitkan Tuhan. Phrase Noun Phrase Ps. CN 12. Kalau membaca kitab Ruth saya membacanya lebih atau membaca alkitab lebih ke personal approach, pendekatan pribadi, lebih ke aplikasi Phrase Noun Phrase Ps. PM 13. Saudara take advantage dari orang itu. Ambil keuntungan daripada orang itu. Phrase Verb Phrase Ps. JR 14. Iblis akan memilikimu, menghancurkan, men-destroy mengahancurkan hidupmu. Word Verb Phrase Ps. PM 15. Sekali lagi kalau saya jadi lawyer-nya Tuhan, pengacaranya Tuhan, saya akan ngomong. Word Hybrid Ps. PM 16. Ini, saudara, saya mau coba pake tulisan supaya bisa lebih di center. Word Hybrid Ps. JM 17. Sebab kalau perkataannya nggak bisa dipegang, kalau selama pacaran aja, preview-nya jelek. Word Hybrid Ps. JR 18. Kalau mereka tahu, itu karena mereka tahu dari watching, dari melihat saja, apa yang ada disekitarnya. Word Verb Ps. JR 19. Puji Tuhan! bisa istirahat. Tapi, mau disuruh 7 kali, 8 kali saya enjoy dan kalau sampai senin saya pulang, selasa ngapain lagi? Word Verb Ps. JM From the collection data that has been analyzed, almost of the preachers in MSC insert the linguistic unit English word rather than phrase and also the lexical item that always used by members is noun. To know more detail about insertion see appendix 2. All of the data above is done by preachers in formal situation where they delivering their sermon. It is irrelevant with theory from (Cakrawarti, 2001, p. 17) which said that code mixing from situation point of view is in informal situation. Then, from the data above, the preachers inserts type of code mixing especially noun to show that they are bilinguals and educated people. It means that, they know how to use English language and mix the language in Indonesian and in formal situation. Their mixing in formal situation has function, for the example is from datum 1 about the word “romance”. The preacher used the word “romance” rather than used Indonesian “percintaan”. It has shown that those word has high function where it suitable for delivering a sermon because the word relates with Holy Bible. In the context he wanted to explain that the book of Ruth in the bible is not only about the story of love between human but also between God and us (people) and also it is more romantic and subtler rather than use Indonesia word “percintaan”. It is happened because “percintaan” sounds more lust and rude and it is not suitable to use in the relationship between God and human because the love of God is different from human’ love. However, there are many preachers who alternate their language is caused they want to change the topic. The alternation from those examples in code mixing was used as a marker of high social class, as an indication of elite membership and an expression of power and prestige by members of MSC. It is grammatically unconstrained and can be characterized in terms of alternative lexical insertions. In a formal situation, some topics and situations are better suited to the use of one language over another wherein bilingual speakers choose which code to speak depending on where they are and what they are discussing and also expressing respect and deference to others at church. It is also used for powering the maintenance of the communication to their members. From the data that has been collected, all of preachers of MSC use code mixing are in formal situation. Actually it is irrelevant with the theory from Cakrawati. She said that from situation point of view, code mixing is used in informal situation. But, when a person uses code mixng in formal situation, means that they have reasons. However, the researcher has analyzed the data that, there are some reasons why the preachers mix their language and the reasons are appropriate with the theory from Hoffman and Saville-Troike about reason of code mixing that happened in MSC. Conclusion Based on the result of the study, it can be concluded that the members of MSC used code mixing in their utterance. All the data are appropriate with the theory that has been explained in Chapter 2. In this case, preachers of MSC just mix their language with Indonesian and English. Therefore, the types of code mixing are showed as insertion and alternation. Regarding of code mixing categories of insertion, preachers of MSC is more use insertion of noun rather than the others. The linguistic unit of insertion is word and phrase, but from the analysis, members of MSC mostly use insertion of word. Meanwhile alternation is used by preachers in MSC; in the linguistic unit form are sentence and clause. They use this type to alternates their language from Indonesian to English. They use it for changing the topic or used to repeat the previous sentence. Members of MSC are able to alternates from Indonesian to English because from the data that has been analyzed, it has been proved that the Indonesian and English from the utterance of members who use alternate are equivalence. Then for the reason of MSC all the data are appropriate with theory of Hoffman and Sabille-Troike. In fact, when bilingual mix their language sometime they do not realize that they said it because they have a purpose. Besides that they want to show that they are able to speak more than one language, if they do discussion, or give information or express their feeling they use English language. This code mixing also clearly relates with social status where in this case, the preachers in MSC, especially preachers who gives sermon in youth community have a high status because they are from educated and businessman background and they are accustomed to speak with English language every day. Therefore the preachers treats with respect and presumed to be very intelligent by society. The preacher uses English as a language that has a high position as a viable language used to discuss or give knowledge about the Bible. Besides that, in formal language situation, there are rarely mixed code. If there is mix code in the formal situation, it is because there is a purpose or function and also there are no proper expressions in a language that is being used so it is necessary to use words from foreign language and Sometimes there are also mixes the code if the speaker wants to show his knowledge or his position. In conclusion, the preachers in MSC event though they are able to speak more than one language, they have reasons to speak it. They used English language also to examine the contents of the Bible. When she or he gives information or knowledge to their members, they certainly mix their language because they are educated people who know about how to use code mixing in the formal situation. Suggestion Code mixing is interesting objects to be analyzed. In this case, code mixing that has done in MSC is indeed related to the church in every day. Everyone in the church always speaks using Indonesia and English language. Moreover, the member in MSC is almost Indonesian with Chinese descent. This research could be continued to examine in a church where the person is the only Javanese or in traditional church that can speak 2 languages, maybe English and Javanese ??but whether they will use it according to the purpose well or not. References Bhatia, T. K., & Ritchie, W. C. (Eds.). (2006). The Handbook of Bilinguallism. UK: Blackwell Publishing. Cakrawarti, D. A. (2001). Analysis of Code Switching and Code Mixing in the TEENLIT CANTING CANTIQ BY DYAN NURANINDYA. Faculty of Humanities Diponegoro University Semarang. Chaer, A., & Agustina, L. (2004). Sosiolinguistik Perkenalan Awal. Jakarta: Rineka Cipta. Crystal, D. (2010). Little Book of Language. Cambridge: Cambridge University Press. Hoffman, C. (1991). An Introduction to Bilingualism. London: Longman. Incorporated, M. (2004). businessman Maise, M. (2004). Social Status Miles, M. B., & Huberman, A. M. (1992). Qualitative Data Analysis. Newbury Park: SAGE Publications, Inc. Musyken, P. (2000). Bilingual Speech A Typology of Code Mixing Neeley, T. (2009). Global Business Speaks English. Harvard, Harvard. Pardede, H., & Kisno. (2007). Introduction of Sociolinguistics Powell, E. T., & Renner, M. (2003). Analyzing Qualitative Data. Program Development&Evaluation, G3658-12. WiseGeek. (2003). What is Export import Wyk, D. B. v. Research Design and Methods part 1. University of the Western Cape.